Recent progress in photocatalytic conversion of carbon dioxide over gallium oxide and its nanocomposites. (June 2018) - Huang, Zeai; Teramura, Kentaro; Asakura, Hiroyuki; Hosokawa, Saburo; Tanaka, Tsunehiro
Abstract : Photocatalytic conversion of CO2 is a promising method to solve problems of both energy crisis and global climate change. The efficient transfer of solar energy into high-value chemical energy is the ultimate goal of this technology. Gallium oxide is a suitable candidate for the photocatalytic conversion of CO2 due to its ideal band positions. Modification of Ga2 O3 to achieve enhanced photocatalytic activity and understanding the catalytic mechanism are important for the design of high-efficiency photocatalysts.